Leucine-rich repeat kinase 2 positively regulates inflammation and down-regulates NF-κB p50 signaling in cultured microglia cells. Issue 1 (December 2015) - Russo, Isabella; Berti, Giulia; Plotegher, Nicoletta; Bernardo, Greta; Filograna, Roberta; Bubacco, Luigi; Greggio, Elisa
Abstract Background Over-activated microglia and chronic neuroinflammation contribute to dopaminergic neuron degeneration and progression of Parkinson's disease (PD). Leucine-rich repeat kinase 2 (LRRK2), a kinase mutated in autosomal dominantly inherited and sporadic PD cases, is highly expressed in immune cells, in which it regulates inflammation through a yet unclear mechanism. Methods Here, using pharmacological inhibition and culturedLrrk2 − /− primary microglia cells, we validated LRRK2 as a positive modulator of inflammation and we investigated its specific function in microglia cells. Results Inhibition or genetic deletion of LRRK2 causes reduction of interleukin-1β and cyclooxygenase-2 expression upon lipopolysaccharide-mediated inflammation. LRRK2 also takes part of the signaling trigged by α-synuclein fibrils, which culminates in induction of inflammatory mediators. At the molecular level, loss of LRRK2 or inhibition of its kinase activity results in increased phosphorylation of nuclear factor kappa-B (NF-κB) inhibitory subunit p50 at S337, a protein kinase A (PKA)-specific phosphorylation site, with consequent accumulation of p50 in the nucleus. Conclusions Taken together, these findings point to a role of LRRK2 in microglia activation and sustainment of neuroinflammation and in controlling of NF-κB p50 inhibitory signaling. Understanding the molecular pathways coordinated by LRRK2 in activated microglia cells after pathological stimuli such us fibrillar α-synuclein holds the potential to provide novel targets for PD therapeutics.